204k views
23 votes
Pls help with my homework

Pls help with my homework-example-1
User Nockenfell
by
4.4k points

1 Answer

7 votes

Answer:

x^2 + x - 6

Explanation:

The factors are

(x - 2)(x + 3) Notice that the signs change when you write them as factors.

That's because the roots are derived from what will make the factors go to zero.

x - 2 = 0

x = 2 Which is what you were given.

x + 3 = 0

x = - 3 Which is what you were given.

(x - 2 )(x + 3)

x*x = x^2

x*3 = 3x

-2*x = - 2x

-2*3 = - 6

x^2 - 2x + 3x - 6

x^2 + x - 6

So that will be your answer.

User GOVIND DIXIT
by
5.1k points